Silicon-based material, preparation method thereof, and related secondary battery, battery module, battery pack and device

By using silicon-based materials with core-shell structures in secondary batteries, combining the buffering effect of the silicon phase and lithium silicate phase and the isolation effect of the cladding layer, the poor cycle performance caused by the structural instability of the silicon-based materials is solved, and high energy density and balanced battery performance are achieved.

CN116210097BActive Publication Date: 2025-03-07CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202080102787.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-11-12
Publication Date
2025-03-07
Estimated Expiration
2040-11-12

AI Technical Summary

Technical Problem

Due to the large volume changes in the deliquification volume and poor structural stability of silicon-based materials, the circulation performance of secondary batteries is poor, limiting their large-scale application.

Method used

Silicon-based materials using core-shell structures, where the core structure includes the silicon phase and lithium silicate phase. The grain size of the lithium silicate phase is ≥30nm, which can effectively buffer the shrinkage and expansion caused by the deintercalation of lithium ions in the silicon phase, enhance structural stability, and isolate the electrolyte through the cladding layer to reduce the possibility of side reactions.

Benefits of technology

The energy density and cycling performance of the secondary battery are improved, structural and chemical stability are ensured, and the negative impact of lithium loss on battery performance is avoided, achieving a more balanced first-time Coulomb efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116210097B_ABST
    Figure CN116210097B_ABST
Patent Text Reader

Abstract

A silicon-based material, a preparation method thereof, and a related secondary battery (5), a battery module (4), a battery pack (1), and a device. The silicon-based material comprises a core structure and a coating layer disposed on at least a portion of the surface of the core structure; the core structure comprises a silicon phase and a lithium silicate phase, and the grain size P of the lithium silicate phase is ≥30 nm. The silicon-based material, while improving the energy density of the secondary battery (5) through the silicon phase, can also improve the structural stability and chemical stability of the silicon-based material, so that the secondary battery (5) as a whole can present satisfactory and balanced cycle performance and first coulomb efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to a silicon-based material, a preparation method thereof, and related secondary batteries, battery modules, battery packs, and devices. Background Art

[0002] Secondary batteries have been widely used in the new energy industry due to their high energy density, long cycle life, no pollution, no memory effect, etc. For example, with the development of new energy vehicles, the demand for secondary batteries will show explosive growth.

[0003] As people's demand for improving the energy density of secondary batteries increases, the demand for the development of high-capacity materials is becoming more and more urgent. The theoretical specific capacity of silicon-based materials is as high as 3600mAh / g, which is much higher than the specific capacity of graphite carbon materials currently used in commercial applications (~360mAh / g). At the same time, it has the advantage of abundant resources, so it has become the focus of research and development of next-generation materials.

[0004] However, silicon-based materials have poor cycle performance due to large volume changes caused by lithium insertion and extraction (up to 300% for pure silicon) and poor structural stability, which greatly limits their large-scale application. Summary of the invention

[0005] In order to solve the above technical problems, the first aspect of the present application provides a silicon-based material, which includes a core structure and a coating layer arranged on at least a portion of the surface of the core structure; the core structure includes both a silicon phase and a lithium silicate phase, and the grain size P of the lithium silicate phase is ≥30nm.

[0006] The silicon-based material of the present application is a core-shell structure, wherein the core structure includes a silicon phase and a lithium silicate phase. The lithium silicate phase having the above-mentioned grain size can effectively buffer the shrinkage and expansion of the silicon phase when lithium ions are extracted and deintercalated, enhance the structural stability of the silicon phase, and avoid the problem of poor cycle performance of the secondary battery due to the pulverization and collapse of the silicon phase; in addition, the lithium silicate phase of the above-mentioned grain size can also make the silicon-based material have a certain chemical stability, reduce the contact area between the lithium silicate phase and water, air, electrolyte, etc. during the preparation of the secondary battery, reduce the possibility of side reactions, and avoid the negative impact of lithium loss on the cycle performance and the first coulomb efficiency of the secondary battery. Therefore, the silicon-based material of the present application, while improving the energy density of the secondary battery through the silicon phase, can also overcome the defect of the unstable silicon phase structure. By improving the structural stability and chemical stability of the silicon-based material, the secondary battery as a whole can present a satisfactory and balanced cycle performance and the first coulomb efficiency.

[0007] In any embodiment of the present application, 30nm≤P≤500nm; optionally, 30nm≤P≤100nm. The lithium silicate phase satisfying this grain size is conducive to achieving efficient conduction of lithium ions, thereby further improving the cycle performance of the secondary battery.

[0008] In any embodiment of the present application, the grain size of the silicon phase is Q≥10nm; optionally, 50nm≤Q≤300nm. The present application limits the grain size of the silicon phase, thereby making the cycle performance of the secondary battery more outstanding.

[0009] In any embodiment of the present application, the silicon-based material satisfies: 0.5≤Q / P≤5; optionally, 1≤Q / P≤4. The present application can maximize the buffering effect of lithium silicate on the silicon phase when it deforms by controlling the particle size ratio of the silicon phase to the lithium silicate phase in the silicon-based material, further overcoming the defect of poor structural stability of the silicon phase, thereby further improving the cycle performance of the secondary battery.

[0010] In any embodiment of the present application, in the silicon-based material, the molar ratio m of silicon element to lithium element satisfies: 1≤m≤5; optionally, 1≤m≤3. The limitation on the molar ratio of silicon to lithium element can ensure that the silicon phase efficiently improves the energy density of the secondary battery, while effectively reducing the probability of pole piece deformation caused by silicon phase expansion, ensuring the ion conductivity of the pole piece, thereby further improving the cycle performance of the battery.

[0011] In any embodiment of the present application, the volume average particle size Dv of the silicon-based material 50 ≤10μm; optionally, 5μm≤Dv 50 ≤7μm. By controlling the volume average particle size Dv of the silicon-based material 50 , which can further improve the kinetic performance and cycle performance of secondary batteries.

[0012] In any embodiment of the present application, the specific surface area of ​​the silicon-based material is 0.5 m 2 / g-3m 2 / g; Optionally, the specific surface area of ​​the silicon-based material is 0.5m 2 / g-1.5m 2 / g. The silicon-based material of the present application that meets the specific surface area has better structural stability and chemical stability and can efficiently realize lithium ion conduction, thereby making the cycle performance and first coulombic efficiency of the secondary battery more excellent.

[0013] In any embodiment of the present application, the powder tap density of the silicon-based material is 0.6-1.2 g / cm 3 , the compacted density of the powder is 1.0-1.5g / cm 3By limiting the tap density and compaction density of the powder, more silicon-based materials can be contained in the pole piece, thereby improving the energy density of the secondary battery.

[0014] In any embodiment of the present application, lithium silicate includes at least one of Li2Si2O5, Li2SiO3, and Li4SiO4.

[0015] In any embodiment of the present application, the material of the coating layer includes at least one of a carbon-based material, an organic polymer, a metal and a metal oxide. The selection of the coating layer material of the present application can effectively prevent the electrolyte from entering the coating layer and contacting the core, thereby avoiding the electrolyte from reacting with the silicon phase and the lithium silicate phase to cause lithium loss.

[0016] In any embodiment of the present application, the coating layer has a thickness of ≤30 nm, which can effectively isolate the electrolyte from the core and ensure that lithium ions can quickly pass through the coating layer and be deintercalated on the silicon phase, which is beneficial to improving the cycle performance of the secondary battery.

[0017] The second aspect of the present application is to provide a method for preparing a silicon-based material, comprising the following steps:

[0018] 1) adding silicon dioxide, metallic lithium and a complexing agent into an ether solvent and filtering the mixture, and subjecting the filtered solid phase system to heat treatment to obtain primary precursor particles;

[0019] 2) adding the primary precursor particles into a mixed solution of ethanol and water, and filtering to obtain secondary precursor particles;

[0020] 3) coating the secondary precursor particles to obtain a silicon-based material;

[0021] The silicon-based material comprises a core structure and a coating layer disposed on at least a portion of the surface of the core structure; the core structure comprises both a silicon phase and a lithium silicate phase, and the grain size P of the lithium silicate phase is ≥30 nm.

[0022] The above preparation method is simple, safe and efficient, and can obtain silicon-based materials including silicon phase and lithium silicate phase with excellent structural stability and chemical stability. Therefore, while the energy density is improved, the cycle performance and first coulombic efficiency of the secondary battery also have a relatively balanced performance.

[0023] In any embodiment of the present invention, in step 1), the mass ratio of silicon oxide to metallic lithium is 1:(0.03-0.16); optionally, the mass ratio of silicon oxide to metallic lithium is 1:(0.05-0.16). By controlling the ratio of silicon oxide to metallic lithium, the ratio of silicon phase to lithium silicate phase in the core structure of silicon-based material can be controlled, so that the silicon-based material can achieve efficient improvement of energy density of secondary battery on the basis of certain structural stability.

[0024] In any embodiment of the present application, in step 1), the temperature of the heat treatment is ≥ 600°C; optionally, the temperature of the heat treatment is 700°C-900°C.

[0025] In any embodiment of the present application, in step 1), the heat treatment time is ≥ 0.5 h; optionally, the heat treatment time is 1 h-3 h.

[0026] By further limiting the heat treatment temperature and time, the particle sizes of the silicon phase and the lithium silicate phase in the silicon-based material can be optimized so that the particle sizes of the two have better matching, which is beneficial to improving the cycle performance and first coulombic efficiency of the secondary battery.

[0027] In any embodiment of the present application, in step 2), the primary precursor particles are stirred in the mixed solution for at least 12 hours and filtered to obtain secondary precursor particles; alternatively, the primary precursor particles are stirred in the mixed solution for 12 hours to 24 hours. The stirring time is conducive to the conversion of silicon dioxide and metallic lithium into silicon phase and lithium silicate phase, ensuring the efficient preparation of silicon-based materials.

[0028] In any embodiment of the present application, in step 3), the temperature of the coating treatment is ≤800°C, and optionally, the temperature of the coating treatment is 600°C-800°C.

[0029] In any embodiment of the present application, in step 3), the coating treatment time is ≤6h; optionally, the coating treatment time is 0.5h-3h.

[0030] The above-mentioned coating temperature and coating time can achieve coating of the core structure while avoiding further increase of the grain size of the silicon phase and the lithium silicate phase in the core structure, which is beneficial to further improve the cycle performance and the first coulombic efficiency of the secondary battery.

[0031] In any embodiment of the present application, the mass ratio of the primary precursor particles to the ethanol / water solution is 0.01-0.1. This mass ratio can further remove the unreacted metallic lithium in the system, and prevent the silicon-based material from reacting with water, electrolyte, etc. during the assembly of the secondary battery, thereby affecting the energy density, cycle performance, and first coulombic efficiency of the secondary battery.

[0032] The third aspect of the present application is to provide a secondary battery, which comprises the silicon-based material of the first aspect or the silicon-based material prepared by the preparation method of the second aspect. The secondary battery has a high energy density, and the cycle performance and the first coulombic efficiency are also relatively balanced.

[0033] The fourth aspect of the present application is to provide a battery module, which includes the secondary battery of the third aspect. Therefore, the battery module has a relatively high energy density while also having a relatively balanced cycle performance and first coulombic efficiency.

[0034] The fifth aspect of the present application is to provide a battery pack, which includes the battery module of the fourth aspect. Therefore, while the battery pack has a high energy density, the cycle performance and the first coulombic efficiency are also relatively balanced.

[0035] The sixth aspect of the present application is to provide a device, which includes at least one of the secondary battery of the third aspect, the battery module of the fourth aspect, and the battery pack of the fifth aspect. The device has the characteristics of good endurance and long service life, and high user satisfaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.

[0037] Figure 1 is a schematic diagram of one embodiment of a secondary battery;

[0038] Figure 2 yes Figure 1 Exploded diagram of

[0039] Figure 3 is a schematic diagram of an embodiment of a battery module;

[0040] Figure 4 is a schematic diagram of an embodiment of a battery pack;

[0041] Figure 5 yes Figure 4 Exploded diagram of

[0042] Figure 6 is a schematic diagram of an embodiment of a device in which a secondary battery is used as a power source;

[0043] Figure 7 is the XRD pattern of the silicon-based material of Example 1;

[0044] Figure 8 This is the SEM image of the silicon-based material of Example 1. DETAILED DESCRIPTION

[0045] In order to make the purpose, technical solutions and advantages of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below in combination with the embodiments of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0046] Silicon-based materials

[0047] The embodiment of the first aspect of the present application provides a silicon-based material, including a core structure and a coating layer arranged on at least a portion of the surface of the core structure; the core structure includes both a silicon phase and a lithium silicate phase, and the grain size P of the lithium silicate phase is ≥30nm.

[0048] In the core structure of the silicon-based material of the present application, the silicon phase is used to achieve an increase in energy density. In order to overcome the defect of poor structural stability of the silicon phase, a lithium silicate phase with a grain size of P ≥ 30nm is distributed around the silicon phase. The lithium silicate phase of this size can act as a buffer to effectively reduce the contraction and expansion of the silicon phase when lithium ions are extracted and inserted, giving the silicon phase more mechanical support and reducing the collapse and pulverization of the silicon phase, so that the silicon-based material has a relatively satisfactory structural stability while having a high energy density, which is conducive to ensuring the cycle performance of the secondary battery.

[0049] The silicon-based material of the present application can also improve the first coulombic efficiency of the secondary battery. Based on this phenomenon, the inventor analyzed and believed that it might be that during the preparation process of the secondary battery, a part of the silicon-based material will inevitably come into contact with active components such as water and electrolyte, and compared with the lithium silicate phase with a small grain size, when the grain size P of the lithium silicate phase is ≥30nm, the chemical stability of the material is better, thereby achieving an improvement in the first coulombic efficiency of the secondary battery.

[0050] In addition to improving the structural stability and chemical stability of silicon-based materials, the lithium silicate phase can also act as a lithium ion conductor to enable lithium ions to be inserted and removed from the silicon phase, thereby further improving the cycle performance of the secondary battery.

[0051] Since the silicon-based material of the present application is a core-shell structure, that is, at least a portion of the outer surface of the core structure has a coating layer, the coating layer can effectively isolate the electrolyte from the core structure, especially avoiding the contact reaction between the electrolyte and the silicon phase, so that the silicon phase can retain more sites for embedding lithium ions, and can also avoid the increased lithium consumption caused by the repeated formation of the SEI film due to the possible pulverization of the silicon phase. Therefore, the present application controls the structure and composition of the silicon-based material, so that the silicon-based material can improve the energy density of the secondary battery while also balancing the cycle performance and the first coulomb efficiency of the secondary battery.

[0052] In some embodiments, the grain size of the lithium silicate phase satisfies the range: 30nm≤P≤500nm, for example, 30nm≤P≤480nm, 50nm≤P≤200nm, 40nm≤P≤300nm, 150nm≤P≤250nm, 30nm≤P≤90nm, etc. When the grain size of the lithium silicate phase is within the above range, it can not only better cope with the deformation of the silicon phase, further reduce the probability of pulverization and collapse of the silicon phase, but also increase the transmission speed of lithium ions in the lithium silicate phase, thereby further optimizing the cycle performance of the secondary battery. Optionally, the grain size of the lithium silicate phase can generally be controlled to be 30nm≤P≤100nm, for example, 40nm≤P≤70nm.

[0053] In some embodiments, the lithium silicate phase may include at least one of Li2Si2O5, Li2SiO3, and Li4SiO4.

[0054] In addition to limiting the grain size of the lithium silicate phase, the present application can further improve the electrical performance of the secondary battery by limiting the grain size of the silicon phase.

[0055] In some embodiments, the grain size of the silicon phase is Q ≥ 10 nm; optionally, 10 nm ≤ Q ≤ 300 nm. When the grain size of the silicon phase is within the given range, the structural stability of the material can be further improved, and the lithium ion transmission speed can be further increased, thereby further improving the cycle performance of the battery.

[0056] The grain size in this application is calculated by using the Scherrer formula after analyzing the physical composition of the material using an X-ray diffractometer, measuring the diffraction angle of the strongest peak of the Si phase and the half-width of the diffraction peak, and using the Scherrer formula.

[0057] Scherrer formula is: D = Kγ / B / Cosθ,

[0058] Where D is the grain size, K is the Scherrer constant, which is 0.89; γ is the X-ray diffraction wavelength, which is 0.154056nm; B is the half-height width of the diffraction peak (converted to radians, radians = angle / 180°*3.14), and θ is the diffraction angle. For silicon phase, Li2Si2O5, Li2SiO3 and Li4SiO4 phases, the main diffraction peaks corresponding to diffraction angles of 28.5±0.5°, 24.7±0.5°, 26.9±0.5° and 22.2±0.5° are selected for grain size calculation.

[0059] In some embodiments, the grain size ratio Q / P of the silicon phase and the lithium silicate phase in the silicon-based material is 0.5-5. When Q / P is within the given range, the expansion and contraction of the silicon phase can be alleviated to a large extent by the surrounding lithium silicate phase, which can better cope with the deformation of the silicon phase, significantly reduce the probability of pulverization and collapse of the silicon phase, further improve the structural stability of the material, and make the secondary battery show more satisfactory cycle performance. Optionally, 1≤Q / P≤4.

[0060] In some embodiments, the molar ratio m of silicon to lithium elements in the silicon-based material of the present application satisfies 1≤m≤5. Based on the above, the silicon phase is mainly used to improve the energy density of the silicon-based material, and the lithium silicate phase is used to buffer the deformation of the silicon phase and reduce the possibility of its pulverization and collapse. Therefore, by controlling the ratio of silicon to lithium elements in the silicon-based material, the positive and negative effects of the silicon phase can be balanced, that is, the silicon-based material is guaranteed to have a relatively high and satisfactory energy density, and the silicon-based material will not be easily deformed due to excessive silicon phases, which will affect the cycle performance of the secondary battery. Optionally, 1≤m≤3, at this time, the structural stability of the silicon-based material is better.

[0061] In some embodiments, the volume average particle size D of the silicon-based material of the present application is v50 ≤10μm. When the volume average particle size D v50 When the particle size is ≤10μm, the structural stability of the silicon-based material can be further guaranteed, and the electrolyte will not be consumed excessively, so that the cycle performance of the secondary battery is more balanced; and the appropriate volume average particle size can enable lithium ions to have a suitable diffusion path, thereby further improving the kinetic performance of the battery. Optionally, 5μm≤D v50 ≤7μm.

[0062] In some embodiments, the specific surface area of ​​the silicon-based material of the present application is 0.5 m 2 / g-3m 2 / g, optionally, a specific surface area of ​​0.5m 2 / g-1.5m 2When the specific surface area is within the given range, the structural stability of the silicon-based material can be further improved, the lithium ion conduction efficiency of the silicon-based material can be enhanced, and the excessive loss of lithium can be suppressed, which is beneficial to further improve the secondary battery cycle performance and the first coulomb efficiency.

[0063] In some embodiments, the tap density of the silicon-based material of the present application is 0.6-1.2 g / cm 3 .

[0064] In some embodiments, the powder compaction density of the silicon-based material of the present application is 1.0-1.5 g / cm 3 When the tap density and / or compaction density is within the given range, it can ensure that more silicon-based materials are attached to the current collector per unit area, thereby achieving a significant increase in the energy density of the secondary battery.

[0065] In the silicon-based material of the present application, there is no specific limitation on the material of the coating layer coated on at least part of the surface of the core structure, as long as it can block the entry of the electrolyte, realize the conduction of lithium ions and the reduction potential is lower than the reduction potential of the silicon phase. For example, it can be selected from at least one of carbon-based materials, organic polymers, metals and metal oxides. Exemplarily, it can be alkanes, olefins, alkynes, carbon nanotubes, carbon fibers, graphene, polyacrylonitrile, resorcinol, silane, Cu, Ni, TiO2, Al2O3, etc.

[0066] In addition, the thickness of the coating layer of the silicon-based material is ≤30nm. This thickness can effectively isolate the electrolyte from the core structure, inhibit excessive lithium loss by reducing the contact area between the silicon phase, lithium silicate phase and the electrolyte, and enable lithium ions to pass quickly and efficiently complete the insertion or extraction of lithium, thereby further improving the initial coulombic efficiency and cycle performance of the secondary battery.

[0067] The second aspect of the present application provides a method for preparing a silicon-based material, comprising the following steps:

[0068] 1) adding silicon dioxide, metallic lithium and a complexing agent into an ether solvent and filtering the mixture, and subjecting the filtered solid phase system to heat treatment to obtain primary precursor particles;

[0069] 2) adding the primary precursor particles into a mixed solution of ethanol and water, and filtering to obtain secondary precursor particles;

[0070] 3) coating the secondary precursor particles to obtain a silicon-based material;

[0071] The silicon-based material comprises a core structure and a coating layer disposed on at least a portion of the surface of the core structure; the core structure comprises both a silicon phase and a lithium silicate phase, and the grain size P of the lithium silicate phase is ≥30 nm.

[0072] In step 1), silicon dioxide, metallic lithium and a complexing agent are mixed and stirred with an ether solvent. As the stirring proceeds, metallic lithium and silicon dioxide gradually form a bonding relationship, wherein the longer the stirring time, the more metallic lithium is bonded to silicon dioxide. The mixed solution is then filtered, and the solid phase system obtained by filtration is heat-treated to obtain primary precursor particles. The above-mentioned heat treatment step can not only convert the solid phase system into a silicon phase and a lithium silicate phase, but also control the grain size P ≥ 30nm of the lithium silicate phase. The ether solvent of the present application contributes to the solubility and dispersibility of each raw material.

[0073] In some embodiments, the heat treatment may be performed in a tube furnace filled with argon.

[0074] It should be noted that in step 1), the process of mixing silicon dioxide, metallic lithium and the complexing agent with the organic solvent should be carried out under an inert gas protective atmosphere, for example, it can be carried out under an argon environment with an oxygen content of ≤100 ppm.

[0075] In addition, the solid phase system obtained by filtration can be washed 3-5 times with ethylene glycol dimethyl ether to remove the complexing agent therein, and then dried at 50° C.-70° C. before heat treatment.

[0076] Step 2) is used to improve the conductivity of silicon-based materials. Specifically, there will be some unreacted metallic lithium in the primary precursor particles in step 1). In order to prevent the residual metallic lithium from coming into contact with water or heat during the preparation of the secondary battery and possibly generating lithium oxide that affects the conductivity of the silicon-based material, it is necessary to remove lithium from the primary precursor particles.

[0077] Specifically, the primary precursor particles are added into a mixed solution of ethanol and water to dissolve the residual lithium, and the solution is filtered and collected to obtain the secondary precursor particles.

[0078] In some embodiments, after the primary precursor particles are added to the mixed solution of ethanol and water, the residual lithium is dissolved as completely as possible by controlling the stirring time to be no less than 12 hours, for example, 12 hours to 24 hours.

[0079] Step 3) is to coat the secondary precursor particles. The specific coating method can be determined according to the coating temperature, the selection of the coating agent (at least one of carbon-based materials, organic polymers, metals, and metal oxides), etc. For example, the common vapor phase chemical deposition method, spray drying method, liquid phase reduction method, sol-gel method, etc. in the art can be used.

[0080] Furthermore, the secondary precursor particles may be dried at 500° C.-800° C. and then subjected to coating treatment.

[0081] The preparation method sequentially obtains a silicon-based material with a core-shell structure that can achieve balanced and satisfactory performance in energy density, cycle performance and first coulomb efficiency of a secondary battery through the processes of pre-embedding lithium, heat treatment, residual lithium removal and coating treatment. The core structure of the silicon-based material includes a silicon phase and a lithium silicate phase with a grain size of P≥30nm. The method is simple, easy to operate, safe and efficient, and suitable for large-scale promotion and application.

[0082] In some embodiments, the heat treatment temperature in step 1) is not less than 600°C, for example, 600°C-1000°C; alternatively, the heat treatment temperature is 700°C-900°C.

[0083] In some embodiments, the heat treatment time in step 1) is not less than 0.5 h, for example, 0.5 h to 12 h; optionally, the heat treatment time is 1 h to 3 h.

[0084] By adjusting within the above temperature and time ranges, the grain size P of lithium silicate and the grain size Q of silicon phase can be further controlled. During the preparation process, the different qualities of silicon oxide, metallic lithium and complexing agent, as well as different complexing agents, organic solvents, and even the difference in stirring time before heat treatment will affect the grain size of silicon phase and lithium silicate phase in the primary precursor particles. The temperature and time can basically further improve the structural stability and chemical stability of silicon-based materials, thereby making the electrical performance of secondary batteries better. For example, in this embodiment, 30nm≤P≤500nm, Q≥10nm, and 0.5≤Q / P≤5 can be achieved. On the basis of the above-defined temperature and time, as the heat treatment temperature increases and the time is extended, the grain size of the lithium silicate phase will tend to increase.

[0085] In some embodiments, the mass ratio of silicon oxide to metallic lithium in step 1) is 1:(0.03-0.16); alternatively, the mass ratio of silicon oxide to metallic lithium is 1:(0.05-0.16). This ratio helps to control the mass ratio of silicon phase and lithium silicate phase in the core structure of silicon-based materials, thereby enabling silicon-based materials to have a higher energy density on the basis of certain structural stability and chemical stability, thereby further improving the electrical performance of secondary batteries and overcoming the defects caused by silicon phase. For example, by controlling the mass ratio of silicon oxide to metallic lithium, the molar ratio m of silicon element to lithium element in silicon-based materials can be in the range of 1-5.

[0086] In addition, the ether solvent in step 1) may be ethylene glycol dimethyl ether and / or ethylene glycol diethyl ether.

[0087] The complexing agent in step 1) can be an aromatic solvent, and optionally, can be at least one of benzene, biphenyl, naphthalene, and anthracene. Further, based on the organic solvent, the concentration of the complexing agent is 0.01-0.5 mol / L, that is, 0.01-0.5 mol of the complexing agent can be added to every 1 L of organic solvent.

[0088] When the ether solvent and / or the complexing agent are multiple compounds, the present application does not limit the ratio between the various compounds.

[0089] In some embodiments, in step 3), the coating treatment temperature is ≤ 800°C, and optionally, the coating treatment temperature is 600°C-800°C.

[0090] In some embodiments, the coating treatment time is ≤6h; optionally, the coating treatment time is 0.5h-3h.

[0091] The inventors found that the temperature and time of the coating treatment will affect the grain size of the silicon phase and the lithium silicate phase in the secondary precursor particles. Controlling the temperature and time of the coating treatment within the above range can help make the grain size of the silicon phase and the lithium silicate phase in the material within the given range.

[0092] In some embodiments, in the mixed solution of ethanol and water in step 2), the volume ratio of ethanol to water is (1-5) : 1, which is conducive to making the process of removing residual lithium more gentle. Further, when the mass ratio of the primary precursor particles, the mixed solution of ethanol and water is (0.01-0.1) : 1, the residual lithium in the primary precursor particles will be removed more thoroughly.

[0093] Secondary battery

[0094] The third aspect of the present application provides a secondary battery, which includes the silicon-based material of the first aspect or the silicon-based material prepared by the preparation method of the second aspect.

[0095] Since the secondary battery of the present application adopts the silicon-based material of the first aspect of the present application or the silicon-based material obtained by the preparation method of the second aspect, it has a high energy density while also taking into account the balanced performance of cycle performance and first coulombic efficiency.

[0096] Specifically, the silicon-based material of the first aspect of the present application or the silicon-based material prepared in the second aspect is used as a negative electrode active material in the negative electrode plate of the secondary battery of the third aspect of the present application. In addition, the secondary battery also includes a positive electrode plate and an electrolyte. During the battery charging and discharging process, active ions are embedded and removed back and forth between the positive electrode plate and the negative electrode plate. The electrolyte plays the role of conducting ions between the positive electrode plate and the negative electrode plate.

[0097] [Negative electrode]

[0098] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, and the negative electrode film layer includes the silicon-based material described in the first aspect of the present application.

[0099] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0100] In the secondary battery of the present application, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene PP, polyethylene terephthalate PET, polybutylene terephthalate PBT, polystyrene PS, polyethylene PE and its copolymers, etc.).

[0101] In the secondary battery of the present application, the negative electrode film layer generally comprises a negative electrode active material and an optional binder, an optional conductive agent and other optional auxiliary agents, and is generally formed by coating and drying a negative electrode slurry. The negative electrode slurry coating is generally formed by dispersing the negative electrode active material and the optional conductive agent and binder in a solvent and stirring them uniformly. The solvent may be N-methylpyrrolidone (NMP) or deionized water.

[0102] As an example, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0103] As an example, the binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0104] Other optional auxiliary agents include, for example, thickeners (such as sodium carboxymethyl cellulose CMC-Na).

[0105] In the secondary battery of the present application, the negative electrode film layer may optionally include a certain amount of other commonly used negative electrode active materials, such as other artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate, in addition to the silicon-based materials described in the first aspect of the present application or the silicon-based materials obtained by the preparation method described in the second aspect, wherein the other silicon-based materials may be selected from one or more of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from one or more of elemental tin, tin-oxygen compounds, and tin alloys.

[0106] [Positive electrode]

[0107] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.

[0108] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0109] In the secondary battery of the present application, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene PP, polyethylene terephthalate PET, polybutylene terephthalate PBT, polystyrene PS, polyethylene PE and its copolymers, etc.).

[0110] In the secondary battery of the present application, the positive electrode active material may adopt the positive electrode active material for secondary batteries known in the art. For example, the positive electrode active material may include one or more of one or more of lithium-containing phosphates of olivine structure, lithium transition metal oxides and their respective modified compounds. However, the present application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for secondary batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.5 Co 0.2 Mn0.3 O2(NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2(NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 C0 0.1 Mn 0.1 O2 (NCM811)), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, one or more of lithium iron phosphate (such as LiFePO4 (LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0111] In some preferred embodiments, in order to further improve the energy density of the battery, the positive electrode active material includes one or more of the lithium transition metal oxides and modified compounds thereof as shown in Formula 1,

[0112] Li a Ni b Co c M d O e A f Formula 1,

[0113] In Formula 1, 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1; M is selected from one or more of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B, preferably one or more of Mn and Al; A is selected from one or more of N, F, S and Cl, preferably F.

[0114] The above-mentioned modified compound can be used to perform doping modification and / or surface coating modification on the positive electrode active material.

[0115] In some embodiments, the positive electrode film layer may also optionally include a binder. The type of binder is not specifically limited, and those skilled in the art may select it according to actual needs. As an example, the binder for the positive electrode film layer may include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin One or more.

[0116] In some embodiments, the positive electrode film layer may further include a conductive agent. There is no specific limitation on the type of the conductive agent, and those skilled in the art may select the conductive agent according to actual needs. As an example, the conductive agent used for the positive electrode film layer may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0117] The positive electrode sheet can be prepared according to methods known in the art. As an example, the positive electrode active material, the conductive agent and the binder can be dispersed in a solvent (such as N-methylpyrrolidone, referred to as NMP) to form a uniform positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet is obtained.

[0118] [Electrolytes]

[0119] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be selected from at least one of a solid electrolyte and a liquid electrolyte (i.e., an electrolyte).

[0120] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0121] In some embodiments, the electrolyte salt can be selected from one or more of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalatoborate), LiBOB (lithium dioxalatoborate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorobis(oxalatophosphate)) and LiTFOP (lithium tetrafluorooxalatophosphate).

[0122] In some embodiments, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0123] In some embodiments, the electrolyte may also optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, additives that improve battery low temperature performance, etc.

[0124] [Isolation film]

[0125] Secondary batteries using electrolytes and some secondary batteries using solid electrolytes also include a separator. The separator is arranged between the positive electrode plate and the negative electrode plate to play an isolating role. The present application has no particular restrictions on the type of separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected. In some embodiments, the material of the separator may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer can be the same or different.

[0126] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0127] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0128] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.

[0129] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.

[0130] In some embodiments, reference Figure 2, the outer package may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate are enclosed to form a accommodating cavity. The shell 51 has an opening connected to the accommodating cavity, and the cover plate 53 can be covered on the opening to close the accommodating cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the accommodating cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, which can be adjusted according to needs.

[0131] Battery Module

[0132] The fourth aspect of the present application provides a battery module, which includes the secondary battery of the third aspect.

[0133] Since the battery module of the present application adopts the secondary battery of the third aspect of the present application, it has a high energy density while also taking into account the balanced performance of cycle performance and first coulombic efficiency.

[0134] In some embodiments, the battery module is assembled from secondary batteries. The battery module may contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.

[0135] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0136] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0137] Battery Pack

[0138] The fifth aspect of the present application provides a battery pack, which includes the battery module of the fourth aspect.

[0139] Since the battery pack of the present application adopts the battery module of the fourth aspect of the present application, it has a high energy density while also taking into account the balanced performance of cycle performance and first coulombic efficiency.

[0140] In some embodiments, a battery pack is assembled from battery modules, and the number of battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack.

[0141] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0142] Device

[0143] The sixth aspect of the present application provides a device, the device comprising at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the device, and can also be used as an energy storage unit for the device. The device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0144] The device can select a secondary battery, a battery module or a battery pack according to its usage requirements.

[0145] Figure 6 The device is used as an example. The device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the device's requirements for high power and high energy density of secondary batteries, a battery pack or a battery module can be used.

[0146] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be light and thin, and a secondary battery may be used as a power source.

[0147] Example

[0148] Example 1

[0149] Preparation of silicon-based materials

[0150] 1) Under argon protection (oxygen content ≤ 100 ppm), a certain amount of silicon dioxide, metallic lithium (see Table 1) and 15 g of biphenyl were added to 1 L of ethylene glycol dimethyl ether and stirred for 12 h, filtered, and the solid phase system obtained by filtration was heat-treated in a tubular furnace with argon to obtain primary precursor particles;

[0151] The heat treatment temperature is 600°C and the heat treatment time is 12h;

[0152] 2) adding the primary precursor particles into an ethanol / water solution (volume ratio 3:1), stirring for 24 hours and filtering to obtain secondary precursor particles, and drying at 70° C.;

[0153] 3) The secondary precursor particles are coated with a carbon-based material to obtain a silicon-based material. The coating temperature is 700° C. and the coating time is 2 hours.

[0154] Preparation of electrode sheets

[0155] Add silicon-based material, graphite, sodium carboxymethyl cellulose (CMC, bonding strength) and Super-P conductive agent in a mass ratio of 2:6:1:1 to deionized water and stir continuously to obtain a uniform negative electrode slurry. Use a scraper to apply the negative electrode slurry on the surface of the copper foil and put it into a blast oven at 80°C for drying. Use a punch to punch the electrode into small discs with a diameter of 14 mm to obtain the final circular electrode electrode. The compaction density of the electrode electrode is 1.6 g / cm 3 , surface density is 8mg / cm 2 .

[0156] Preparation of button cells

[0157] The circular electrode plate (positive electrode plate) of the silicon-based material prepared above and the circular lithium negative electrode plate were assembled into a button-type half-cell to characterize its electrochemical performance.

[0158] In a glove box filled with Ar gas, the circular electrode plate of silicon-based material, the circular lithium negative electrode plate, the separator, the electrolyte and the button battery shell are assembled into the final button half-cell. The separator is Celgard 2200 model, and the electrolyte is 1M LiPF6 dissolved in EC: DMC: EM: FEC (volume ratio 30: 30: 30: 10).

[0159] The preparation steps of Example 2-15 and Comparative Example 1-2 are similar to those of Example 1, except that the parameters of the silicon-based material are adjusted.

[0160] The product parameters of each embodiment and comparative example are shown in Table 1.

[0161] Figure 7 This is the XRD spectrum of the silicon-based material of Example 1. Comparing the spectrum with the standard spectrum of lithium silicate and silicon, it is shown that the silicon-based material of this example contains Si, Li2Si2O5 and Li2SiO3 phases.

[0162] Figure 8 : is a SEM picture of the silicon-based material of Example 1. According to the picture, it can be seen that the average particle size of the silicon-based material of Example 1 is less than 10 μm.

[0163]

[0164]

[0165] In Table 1, the detection methods of relevant parameters are as follows:

[0166] 1. Grain size

[0167] The phase composition of the material was analyzed using an X-ray diffractometer. The diffraction angles of the strongest peaks of the Si phase and the lithium silicate phase and the half-width of the diffraction peaks were measured, and the grain sizes of the Si phase and the lithium silicate phase were calculated using the Scherrer formula.

[0168] Scherrer formula is: D = Kγ / B / Cosθ,

[0169] Where D is the grain size, K is the Scherrer constant, which is 0.89; γ is the X-ray diffraction wavelength, which is 0.154056 nm; B is the half-height width of the diffraction peak (converted into radians), and θ is the diffraction angle.

[0170] 2. The molar ratio of silicon to lithium is m

[0171] The element contents of Si and Li in the material were measured using an inductively coupled plasma emission spectrometer (ICP). The measured molar content of Si element was divided by the molar content of Li element to obtain the element molar ratio m value.

[0172] 3. Volume average particle size Dv50

[0173] The volume average particle size of the material was measured using a laser particle size analyzer (Mastersizer 2000) in accordance with the GB / T19077-2016 standard.

[0174] 4. Specific surface area BET

[0175] The BET specific surface area of ​​the material was measured using a surface area analyzer (Tri star II) in accordance with GB / T 19587-2004.

[0176] Test example

[0177] The negative electrode sheets and button batteries of Examples 1-15 and Comparative Examples 1-2 were tested for the following parameters, and the results are shown in Table 2.

[0178] 1. Gram capacity and first coulombic efficiency

[0179] At 25℃ and normal pressure, the button cell was charged and discharged using a Blue Battery Tester. The charge and discharge cut-off voltage was set to 0.01-1.5V, and the current density was 100mA / g. The gram capacity of the material is the gram capacity value corresponding to the first charge of the battery to 1.5V, and the first coulomb efficiency of the material is the ratio of the specific capacity of the battery when it is first charged to 1.5V to the specific capacity of the battery when it is first discharged to 0.01V.

[0180] 2. Fully charged pole piece expansion rate

[0181] Use a micrometer to measure the thickness of the initial electrode and the fully charged electrode. The fully charged electrode is the electrode disassembled after the button battery is discharged to 0.01V. The expansion rate of the fully charged electrode is the difference between the thickness of the fully charged electrode and the initial fresh electrode thickness divided by the initial fresh electrode thickness.

[0182] 3. Capacity retention rate

[0183] The ratio of the 100th charge capacity of a button battery to the first charge capacity is used to characterize the cycle performance.

[0184] Table 2

[0185] Gram capacity mAh / g First coulombic efficiency % Full charge pole piece expansion rate % Capacity retention rate % Example 1 570.2 88.3% 25.0% 87.2% Example 2 568.8 86.5% 27.2% 84.4% Example 3 565.7 85.4% 30.6% 81.5% Example 4 559.5 83.9% 33.4% 78.9% Example 5 553.5 82.6% 35.3% 76.7% Example 6 531.9 80.2% 37.6% 75.4% Example 7 575.8 84.1% 27.5% 83.3% Example 8 557.3 92.5% 23.6% 89.5% Example 9 520.3 95.8% 18.3% 94.4% Example 10 543.5 87.6% 28.1% 84.5% Embodiment 11 560.3 87.8% 26.7% 85.5% Example 12 572.6 86.4% 26.4% 86.5% Example 13 563.4 85.3% 27.3% 86.1% Embodiment 14 584.6 82.3% 29.4% 80.1% Embodiment 15 490.7 87.6% 24.1% 86.9% Comparative Example 1 430.4 67.4% 28.2% 57.6% Comparative Example 2 640.8 74.4% 44.5% 67.8%

[0186] According to Table 2, we can see that:

[0187] The grain size of the lithium silicate phase in the silicon-based materials of Examples 1-15 is greater than 30 nm, which can not only effectively buffer the stress generated by the silicon phase, reduce the probability of pulverization and collapse of the silicon phase, but also improve the structural stability of the silicon-based materials. Therefore, compared with Comparative Examples 1-2, the use of the silicon-based materials of Examples 1-13 can enable the battery to have both higher gram capacity and first coulombic efficiency, better cycle performance and lower electrode expansion rate.

[0188] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A silicon-based material comprising a core structure and a coating layer disposed on at least a portion of the surface of the core structure; the core structure comprises a silicon phase and a lithium silicate phase, and the grain size of the lithium silicate phase is 30nm≤P≤500nm, the grain size of the silicon phase is 50nm≤Q≤300nm, and the specific surface area of ​​the silicon-based material is 0.5m 2 / g-3m 2 / g, the powder tap density of the silicon-based material is 0.6g / cm 3 -1.2g / cm 3 .

2. The silicon-based material according to claim 1, wherein 30nm≤P≤100nm.

3. The silicon-based material according to claim 1 or 2, wherein: The silicon-based material meets the following requirements: 0.5≤Q / P≤5.

4. The silicon-based material according to claim 1 or 2, wherein: The silicon-based material satisfies: 1≤Q / P≤4.

5. The silicon-based material according to any one of claims 1 to 4, wherein: In the silicon-based material, the molar ratio m of silicon element to lithium element satisfies: 1≤m≤5.

6. The silicon-based material according to any one of claims 1 to 4, wherein: In the silicon-based material, the molar ratio m of silicon element to lithium element satisfies: 1≤m≤3.

7. The silicon-based material according to any one of claims 1 to 6, wherein: The volume average particle size D of the silicon-based material v50 ≤10μm.

8. The silicon-based material according to any one of claims 1 to 6, wherein: The volume average particle size of the silicon-based material is 5 μm≤D v50 ≤7μm.

9. The silicon-based material according to any one of claims 1 to 8, wherein: The specific surface area of ​​the silicon-based material is 0.5 m 2 / g-1.5m 2 / g.

10. The silicon-based material according to any one of claims 1 to 9, wherein: The powder compaction density of the silicon-based material is 1.0 g / cm 3 -1.5g / cm 3 .

11. The silicon-based material according to any one of claims 1 to 10, wherein: The lithium silicate phase includes at least one of Li2Si2O5, Li2SiO3, and Li4SiO4.

12. The silicon-based material according to any one of claims 1 to 11, wherein: The material of the coating layer includes at least one of a carbon-based material, an organic polymer, a metal and a metal oxide.

13. The silicon-based material according to any one of claims 1 to 12, wherein: The thickness of the coating layer is ≤30nm.

14. A method for preparing a silicon-based material, comprising the following steps: 1) adding silicon dioxide, metallic lithium and a complexing agent into an ether solvent and filtering the mixture, and heat-treating the solid phase system obtained by filtration to obtain primary precursor particles; 2) adding the primary precursor particles into a mixed solution of ethanol and water, and filtering to obtain secondary precursor particles; 3) coating the secondary precursor particles to obtain a silicon-based material; The silicon-based material comprises a core structure and a coating layer disposed on at least a portion of the surface of the core structure; the core structure comprises a silicon phase and a lithium silicate phase at the same time, and the grain size of the lithium silicate phase is 30nm≤P≤500nm, the grain size of the silicon phase is 50nm≤Q≤300nm, and the specific surface area of ​​the silicon-based material is 0.5m 2 / g-3m 2 / g, the powder tap density of the silicon-based material is 0.6g / cm 3 -1.2g / cm 3 .

15. The preparation method according to claim 14, wherein: In step 1), the mass ratio of the silicon monoxide to the metallic lithium is 1:(0.03-0.16).

16. The preparation method according to claim 14, wherein: In step 1), the mass ratio of the silicon monoxide to the metallic lithium is 1:(0.05-0.16).

17. The preparation method according to any one of claims 14 to 16, wherein: In step 1), the temperature of the heat treatment is ≥ 600°C.

18. The preparation method according to any one of claims 14 to 16, wherein: In step 1), the temperature of the heat treatment is 700°C-900°C.

19. The preparation method according to any one of claims 14 to 18, wherein: In step 1), the heat treatment time is ≥ 0.5 h.

20. The preparation method according to any one of claims 14 to 18, wherein: In step 1), the heat treatment time is 1 h to 3 h.

21. The preparation method according to any one of claims 14 to 20, wherein: In step 2), the primary precursor particles are stirred in the mixed solution for at least 12 hours and filtered to obtain secondary precursor particles.

22. The preparation method according to any one of claims 14 to 20, wherein: In step 2), the primary precursor particles are stirred in the mixed solution for 12 h to 24 h.

23. The preparation method according to any one of claims 14 to 22, wherein: In step 3), the coating treatment temperature is ≤800°C; or, the coating treatment time is ≤6h.

24. The preparation method according to any one of claims 14 to 22, wherein: In step 3), the coating treatment temperature is 600° C.-800° C.; or, the coating treatment time is 0.5 h-3 h.

25. The preparation method according to any one of claims 14 to 24, wherein: The mass ratio of the primary precursor particles to the ethanol / water solution is 0.01-0.

1.

26. A secondary battery comprising the silicon-based material according to any one of claims 1 to 13 or the silicon-based material prepared by the method according to any one of claims 14 to 25.

27. A battery module comprising the secondary battery according to claim 26.

28. A battery pack comprising the battery module according to claim 27.

29. An electric device comprising at least one of the secondary battery according to claim 26, the battery module according to claim 27, and the battery pack according to claim 28.

Citation Information

Patent Citations

  • Negative-electrode active material for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery

    CN107112521A

  • Anode active material and preparation method and application thereof

    CN111180693A